2019
DOI: 10.1016/j.tra.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards autonomous vehicles among people with physical disabilities

Abstract: Attitudes of a sample of 211 UK people who are blind concerning autonomous vehicles (AVs), and the determinants of the willingness of people who are blind to travel in AVs, were examined. Participants answered an open-ended question regarding their attitudes towards AVs and the results were analysed using a semi-automated structural topic modelling procedure. Four "topics" emerged from the exercise: (i) "hope" for future independence and freedom to travel offered by AVs to people who are blind, (ii) scepticism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 84 publications
2
47
0
Order By: Relevance
“…Haboucha, Ishaq, and Shiftan (2017) study of 721 US and Israeli drivers found that at least 44% of the sample had severe hesitations about using an AV. Other surveys have produced similar results (see Bennett et al, 2019). Thus, the outcomes to the present study reinforce the observation of Konig and Neumayr (2017) that for all groups, including people who are blind, "the widespread acceptance and hence adoption of this new technology is far from certain" (p. 42).…”
Section: Discussionsupporting
confidence: 84%
“…Haboucha, Ishaq, and Shiftan (2017) study of 721 US and Israeli drivers found that at least 44% of the sample had severe hesitations about using an AV. Other surveys have produced similar results (see Bennett et al, 2019). Thus, the outcomes to the present study reinforce the observation of Konig and Neumayr (2017) that for all groups, including people who are blind, "the widespread acceptance and hence adoption of this new technology is far from certain" (p. 42).…”
Section: Discussionsupporting
confidence: 84%
“…Personal innovativeness (Tech savviness): AVs project an image of technological innovation, which can positively affect tech-savvy individuals' adoption trend [40,90,97]. This means that enthusiasts who are willing to try new technologies before others may perceive greater comfort and safety via AVs [60,121], and are likely to be early AV adopters [13,62,82,92].…”
Section: Psychological Factorsmentioning
confidence: 99%
“…This means that enthusiasts who are willing to try new technologies before others may perceive greater comfort and safety via AVs [60,121], and are likely to be early AV adopters [13,62,82,92]. • Awareness of AVs: Current knowledge about AVs seems to differ considerably across different socio-demographic clusters and might influence adoption likelihoods and concerns [11,97,99,134].…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Conversely, private and highly comfortable autonomous cars which drive themselves while their users can work or sleep, might prompt "people to travel more frequently and across greater distances, " thus fostering commuting, suburbanization, an energy-intensive lifestyle and, in essence, the production of car-centric urban spaces (Hawkins and Nurul Habib, 2019, p. 69). In addition to reshaping the built environment and the geography of housing, the transition to autonomous cars is also likely to reshape urban mobility, particularly in relation to people with disabilities and minors currently not allowed to employ a car (Bennett et al, 2019). Last but not least, the emergence of artificial intelligences in urban transport poses concrete ethical challenges.…”
Section: Urban Artificial Intelligencesmentioning
confidence: 99%